Effect of Low Density Lipoprotein (LDL) to High Density Lipoprotein (HDL) Ratio with Stroke in Adults in Bogor City (Indian Journal of Public Health Research & Development, 2020)
Context: Stroke is one of the main causes of death and neurological disability in Indonesia. Stroke is acerebrovascular disease which increases in number every year. This study aims to determine the effectof the ratio of Low Density Lipoprotein (LDL) to High Density Lipoprotein (HDL) with the incidence ofstroke in the adult population. This study used data from the PTM (non-communicable disease) cohort studyin 2011. The sample in this study was adult population (25-65) years who were respondents to the PTMcohort study in Bogor in 2011 which numbered 1506 and analyzed using regression tests. logistics withstatistical significance are seen based on 95% confidence intervals. Sample prevalence in adult populationin the city of Bogor who suffered a stroke of 1.26%, respondents with a high ratio of LDL to HDL were35.66%. Respondents with a age of sebesar46 years were 34.26% with the highest prevalence of sex inwomen amounting to 53.45% and those with low education were 54.58%, respondents who were obese were27.42%, respondents with high total cholesterol levels were 38, 45% and respondents with high triglyceridelevels of 17.07%. The results showed that there was a significant relationship between the ratio of LDL toHDL and the incidence of stroke with an adjusted prevalence odds ratio of 3.909 (95% CI 1.346-11.354).The high ratio of LDL to HDL is at risk for the incidence of stroke in the adult population.
Keywords: Stroke, LDL to HDL ratio, Logistic Regression